دراسة تحليلية لانعكاسات تقلبات أسعار النفط على الميزان التجاري الجزائري - إسلال، نوال; شنايت، مراد (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة إلى تحديد العلاقة بين تقلبات أسعار النفط والميزان التجاري الجزائري من خلال تحليل تطورات الصادرات والواردات خلال الفترة (2000-2022)، وذلك باستخدام المنهج الوصفي التحليلي من أجل عرض المفاهيم وتحليل البيانات الإحصائية للفترة المدروسة. وقد توصلت الدراسة إلى أن التقلبات التي تحصل في أسعار النفط في الأسواق العالمية ستؤثر على الميزان التجاري الجزائري، ذلك بسبب كون النفط سلعة إستراتيجية تتأثر بعوامل اقتصاديه وسياسية، وتؤثر التقلبات التي تحدث في أسعار النفط على الميزان التجاري من خلال حجم صادرات المحروقات التي تعتبر المصدر الرئيس للعملة الصعبة في الجزائر، والتي بها يتم تغطية فاتورة الواردات وبالتالي فإن هذه التقلبات سواء كانت ارتفاعا أو انخفاضا ستؤدي إلى اختلال الميزان التجاري إما بالفائض أو العجز This study aims to determine the relationship between oil price fluctuations and the Algerian trade balance by analyzing the developments of exports and imports during the period (2000-2022), Using the descriptive analytical approach to present concepts and analyze statistical data for the period studied. The study found that fluctuations in oil prices in world markets will affect the Algerian trade balance, because oil is a strategic commodity influenced by economic and political factors, and fluctuations in oil prices affect the trade balance through the volume of hydrocarbon exports, which are the main source of foreign in Algeria, with which the import bill is covered, so these fluctuations whether up or down, will lead to an imbalance in the trade balance, either by a surplus or a deficit
AN ANALYTICAL STUDY OF THE REPERCUSSIONS OF OIL PRICE FLUCTUATIONS ON THE ALGERIAN TRADE BALANCE DURING THE PERIOD (2000-2022)
مقال
Keywords: النفط; أسعار النفط; الصادرات; الواردات; رصيد الميزان التجاري; The balance of trade balance; Imports; Exports; Oil prices